American religious revivalism in Great Britain, c. 1826-c. 1863 - Carwardine, R (1975)
British religious revivalism in the mid nineteenth century is an undeniably neglected area of study; despite the widespread incidence of revivals, and the vast numbers of men, women and children embraced by evangelical churches, there exists no comprehensive analysis of revivals in these years. Similarly neglected - yet widely recognised as influential in the development of that revivalism - is the impact on the British evangelical community of American revivalistic ideas and practices. By examining the latter, and in particular the British itinerancies of American revivalists, this thesis offers an insight into the extent and organisation of British revivals in a generation when attitudes to conversion and revivals were undergoing fundamental changes. In the 1820s the majority of evangelicals were extremely reluctant to use anything other than the most traditional of 'means' to encourage revivals. By the time of the revival of 1859 a much more 'instrumentalist', calculated and promotional approach to conversion and church recruitment had taken hold. American example transmitted through publications, private letters and the work of visiting Anericans played a significant part in this transition. The main sources used for this study - especially biographies and autobiographies of major evangelical figures, revival sermons and addresses, and the great quarry of material in evangelical periodicals - have made it possible sympathetically, if not uncritically, to examine the evangelical world from within. They have suggested the need to recognise that there existed a world of conversion and revivals with a life of its own. The evangelical was always a member of a wider secular society as well as of his church; but for the most aggressively evangelistic the regeneration of himself and others was his primary object. Once this is understood, simple secular explanations of the outbreak of revivals - economic decline, or the onset of cholera - are seen to be inadequate} the causation of revivals was complex, but the evangelical's search for conversions and his constant expectation of widespread revival were always fundamental ingredients. Chapter one examines the origins of the more 'engineered', new measures revivalism in the United States in the early nineteenth century. It argues that the revival movement originating in upstate New York under the aegis of Charles Grandison Finney has been given too prominent a place in explaining the introduction of this new style revivalism, and that equally important was the stimulus provided by the fast-growing hyper-evangelistic Methodist churches. Moreover, much of this thrust came from urban centres and not, as has been generally assumed, from the frontier and western areas alone. The urban modifications in the methods and style of revivals (betterorganised agencies of conversion, growing refinement and decorum in worship, for instance) are examined, as are the problems of city churches facing a more heterogeneous population than in Protestant small-town America. The chapter concludes with a summary of the incidence of revivals in the generation up to 1857, noting the peaks of the late 1820s and early 1830s, the late 1830s and early 1840s, and the late 1850s; and asserting the everbroadening hold of the new measures during the period. Continued in text ...]